Exploring The Role of Media in Enhancing Problem-Based Learning in Physics: A Systematic Literature Review - Safanah, Almas; Samsudin, Achmad; Aviyanti, Lina; Hasanah, Lilik; Liliawati, Winny; Oktavianty, Erwina (Jurnal Pendidikan Fisika Indonesia, 2025)
Problem-Based Learning (PBL) is a learner-centred model that focuses on solving problems to train students in addressing challenges they face through real-world problem exploration. This review aims to identify research trends, methodologies, physics topics, associated variables, and outcomes in the field. The systematic literature review followed the PRISMA framework, encompassing the stages of identification, screening, eligibility, and inclusion. A total of 67 articles were analyzed. Articles (2020–2024) were selected using Publish or Perish, Scopus, and SINTA, focusing on PBL in physics with media integration and focusing on research trends, methodologies, topics, variables, and outcomes. Eligibility criteria included international language and publication in 2014–2024, while data was analyzed using Excel and visualized with Tableau. Problem-based learning research (2014–2024) focuses on Indonesia, with 2023 as the peak year. Mechanical physics and critical thinking dominate topics and variables, mainly using quantitative methods. Video multimedia is the most common media, highlighting the need to explore innovative media integration in problem-based learning further.  This SLR highlights key research trends and gaps, guiding future studies to enhance problem-based learning through effective media use.